Introduction - Wayside Shrines in India: an everyday defiant religiosity - Larios, Borayin Maitreya; Voix, Raphaël (South Asia multidisciplinary academic journal, 2018)
Drawing on this special issue’s ethnographic data and analysis this introduction aims to offer an analytical framework for understanding the notion of wayside shrines. It does so by defining wayside shrines as sites that enshrine a worshipped object that is immediately adjacent to a public path, visible from it and accessible to any passerby. Further, we argue that wayside shrines are spaces in which we can observe a unique form of everyday religiosity that challenges sedimented discourses and practices at three different scales: at the level of the individual, of the community, and of the state.